The Impact of Fintech Innovation on Bank’s Performance: Evidence from the Kingdom of Bahrain - Naser, Hanan; Sultanova, Gavkhar; Nahar, Shamsun (International Journal of Economics and Financial Issues, 2024)
This study investigates the impact of bank-level Financial Technology (Fintech) innovations on banks’ performance in the Kingdom of Bahrain from 2012-2021. Annual data of banks listed in Bahrain’s Bourse has been utilized to achieve this objective. In addition, bank-level FinTech indices have been constructed by a textual analysis method that assesses input dimensions through 32 keywords under four categories, including artificial intelligence, blockchain, cloud computing, and big data; FinTech output dimension is evaluated through payment and settlement, resource allocation, risk management, and channel construction technology. Using different panel data estimators, such as pooled OLS, fixed effects, random effects, and panel-corrected standard errors linear regression, results show that FinTech innovations increase banks’ performance. In addition, the findings demonstrate that banks’ capital adequacy ratio, earnings ability, total assets, and annual GDP growth rate also significantly positively impact bank performance. Years in business have a significant adverse effect on bank performance. Interestingly, conventional and state-owned banks have a higher positive impact on returns on assets (ROA) than Islamic and privately owned banks. Policymakers and investors should pay close attention to facilitating ongoing FinTech innovations in the Kingdom of Bahrain to create opportunities and build a more inclusive and efficient financial sector.